Hyperammonemia in a girl who inherited a likely pathogenic variant of the ornithine transcarbamylase gene from her asymptomatic father—A peculiar pattern of X‐linked recessive inheritance - Toby Chun Hei Chan; Hoi Ning Cheung; Jasmine Chow; Mei Tik Leung; Sammy Pak Lam Chen; Chi Chung Shek (Clinical Case Reports, 2022)
Abstract A three‐year‐old Chinese girl presented with hyperammonemia was diagnosed biochemically and genetically (heterozygous for a novel likely pathogenic missense variant c.476T>A) as having ornithine transcarbamylase (OTC) deficiency, a rare X‐linked recessive urea cycle disorders. Extensive family genetic screening eventually revealed paternal gonadosomatic mosaicism.